Case report of unicornuate uterus with subfertility - Esanakula, Jahnavi; Kumar, Maheshwari Mohan; Vijay, Asha S.; Rajasekaran, Rajsri Thuthikadu Rajasekaran Thuthikadu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Most often the uterine developmental anomalies are missed until later in life presenting as infertility. This case report is of a couple presented with primary infertility of six years. 3D ultrasonography helps in for clinical suspicion of a uterine anomaly. The wife had a left unicornuate uterus with adequate uterine cavity and right rudimentary horn and also poor ovarian reserve. The husband had astheno-teratozoospermia. After a failed IVF frozen embryo transfer the couple were advised and underwent IVF-ICSI of donor oocytes with husband sperm. One 5AB blastocyst transferred and at 5 weeks and 6 weeks scans gestational sac along with yolk sac and foetal heart pulsations were noted, respectively. Single embryo transfer with good quality blastocyst is preferable for a unicornuate uterus since there is a risk of pre term labour.